Development of Augmented Reality Based Learning Media for Computer Hardware Materials at SMP Santa Monika - Istiqomah, Dara Nur; Astuti, Reni; Santoso, Danar (Journal of Multidiscipline and Collaboration Research, 2024)
This study aims to develop augmented reality-based learning media for computer hardware materials for Grade VII students at SMP Santa Monika. The research method employed is Research and Development (R&D) using the ADDIE design model, which consists of Analysis, Design, Development, Implementation, and Evaluation. The product development subjects include expert validators in media and material: two lecturers in Information Technology Education, one lecturer in Information Technology Education, and an informatics subject teacher. The small-scale and large-scale product testing subjects consist of Grade VII students at SMP Santa Monika, with a total of 40 students. Data collection techniques used in the study include direct communication, indirect communication, and data collection tools such as unstructured interviews, questionnaires, and documentation. Based on the results obtained, the conclusion of this study is that the augmented reality-based learning media developed is feasible for use in the learning process. The validation results from media and material experts achieved an average percentage of 89.75%, categorized as highly feasible. Additionally, the student response questionnaire results in the small-scale trial showed a percentage of 80.33%, while the large-scale trial achieved 89.74%, both categorized as excellent.